Rerepresenting Autonomated Vehicles in a Macroscopic Transportation Model - Török, Árpád; Szalay, Zsolt; Uti, Gábor; Verebélyi, Bence (Periodica Polytechnica Transportation Engineering, 2020)
The main goal of this article is to determine a comprehensive and well applicable model architecture, which is adequate to estimate the system level advantages with regard to automated transportation and which is appropriate to determine possible costs and losses with regard to the approach of such transport modes. In the study the Budapest Transportation Model is applied. Taking autonomous vehicle penetration into account as an external variable, in the analysis a constant growth is assumed in the penetration of automated vehicles. This article has taken the most relevant factors of transportation network into account with regard to automated cars. It is also important to mention that the paper presents the most important modelling phases, where automated cars can be taken into account during the macroscopic modelling process. In the first step of the process during the network definition phase it is possible to consider the effect of automated vehicles on the transport system (e.g. separated routes). The next phase where the effect of automated vehicles should be taken into consideration is the mode choice step (e.g. different demand segments). And finally traffic assignment step, where the effect of automated vehicles can be represented. The easiest way for this is the modification of passenger car units through the parameter of assigned traffic per capacity ratio.